Inland Waterways Transportation in India: Understanding and Meeting Shipper's Service Requirements - Gupta, Aditya (Journal of Commerce and Trade, 2017)
After Raw Materials, Transportation is the single largest component of cost for any company. Transportation is key to existence of any organisation as it delivers the product in the hands of final customer. Supply Chain Managers have to do a fine balance between cost of transportation and service levels. One of the important decisions in transportation is selection of mode of transportation. Inland Waterways transportation (IWT) is the mode of transportation, within a country, where cargo is moved over rivers and canals. As compared to Road and Rail, IWT is more fuel efficient, environment friendly, less capital intensive, safe and possess least external costs. In spite of carrying several advantages and being recurrently used in several countries, the spread of IWT in India is extremely poor. IWT does not contribute even 0.5 per cent of the total Indian freight transportation. This paper attempts to understand the Indian shipper's transportation service requirements and various factors which influence his choice of mode and how IWT in India can realign itself to meet these requirements. The paper provides some of the recommendations for IWT sector to evolve to meet the shipper's service requirements.